Analysis of Variable Compression Ratio Engine Using Biodiesel when Incorporated with Metal Oxides from Chemical and Biological Resources. (30th June 2022) - Anish, M.; Arunkumar, T.; Jayaprabakar, J.; Nivin Joy, T.; Al Obaid, Sami; Alfarraj, Saleh; Raj, M. M.; Markos, Mebratu
Abstract : Specifically, the current investigation will look at the impacts of nanoemulsions such as titanium and zinc oxides as well as plant extracts and a four-stroke D.I.VCR engine for biodiesel that is produced both chemically and biologically on the environment. Meanwhile, when a homogeneous catalyst is used, a substantial volume of wastewater is made available for the separation and cleaning of the biodiesel catalyst. Because of this, waste cooking oil (WCO) was used to make biodiesel, which were then transesterified using heterogeneous base catalysts. This was done for environmental reasons as well as to minimize the cost of producing biodiesel. The D.I variable compression engine's performance and engine parameters, such as brake specific fuel consumption, brake thermal efficiency, and CO, HC, and NOx emissions, were investigated. Nanoparticles have been shown to produce less NOx than pure diesel when combined with zinc oxides that have been biologically generated at the lowest possible concentration. The carbon dioxide emissions from a biologically generated titanium oxide sample are greater than those from the other samples, with Pure Diesel emitting the least amount of CO2. The emission of less oxygen from a Pure Diesel sample and a chemically generated titanium oxide sample showed a pattern that was comparable. A comprehensive study was conducted to examine the performance and emission characteristics of an internal combustion engine with and without the use of nanoadditives, and the findings revealed an astonishing outcome.